A Model for the Professional Training of Future Social Workers - Ridkodubska, Hanna (Pedagogical Discourse, 2025)
The article addresses the issues of training future social workers in higher education institutions on the basis of the praxeological approach, which involves the purposeful integration of theoretical knowledge with practical skills, professional experience, and active learning forms. It highlights contemporary challenges in the professional training of social workers caused by the increasing complexity of social problems, the interdisciplinary nature of professional activity, and the need to develop key professional competencies, in particular communicative, socio-interactive, and reflective competencies, as components of professional readiness of a social work specialist. A structural and functional model of training future social workers is proposed, encompassing three interrelated blocks: strategic, conceptual and methodological, and criteria and diagnostic. The strategic block defines the social demand for a social work specialist, the goals and objectives of professional training, as well as the guiding principles for the formation of professional competencies focused on effective interaction with various social groups and clients. The conceptual and methodological block outlines pedagogical conditions, forms, methods, and learning technologies aimed at developing practical skills, professional mobility, and social activity of higher education students. Particular attention is paid to the combination of traditional and innovative teaching methods, the use of practice-oriented technologies, the case method, training-based forms of work, modeling of professional situations, and the organization of various types of practical training. The criteria and diagnostic block includes components, criteria, and levels for assessing the formation of professional competencies of future social workers, which makes it possible to determine the effectiveness of the educational process and the level of students’ readiness to carry out professional activities in the context of real social challenges. The article substantiates the expediency of integrating cognitive, activity-communicative, motivational-stimulating, and reflective-evaluative components in the process of professional training, which ensures the integrity and systemic nature of competency formation in future social workers. Special emphasis is placed on developing the ability for effective interpersonal and interprofessional interaction, applying interdisciplinary approaches, and using innovative educational technologies that contribute to the development of professional identity and social responsibility of the specialist. The proposed model of training future social workers is adaptive, ensures the systematic and consistent professional development of higher education students, and meets contemporary requirements of the social sphere. The article may be useful for academic and teaching staff, higher education students, and social work practitioners interested in implementing practice-oriented models of professional training for social workers.